To be an American : cultural pluralism and the rhetoric of assimilation - Hing, Bill Ong (Critical America., 1997)
The impetus behind California's Proposition 187 clearly reflects the growing anti-immigrant sentiment in this country. Many Americans regard today's new immigrants as not truly American, as somehow less committed to the ideals on which the country was founded. In clear, precise terms, Bill Ong Hing considers immigration in the context of the global economy, a sluggish national economy, and the hard facts about downsizing. Importantly, he also confronts the emphatic claims of immigrant supporters that immigrants do assimilate, take jobs that native workers don't want, and contribute more to the.